Postprandial Plasma Amino Acid Responses Between Standard Whey Protein Isolate and Whey Protein Isolate Plus Novel Technology. (February 2019) - Sharp, Matthew H; Stefan, Matthew W; Lowery, Ryan P; Wilson, Jacob M
Background: Muscle mass is an important determinant of metabolic health and physical function. It has previously been demonstrated that the postprandial rise in circulating essential amino acids (EAA) acts as the main stimulus for muscle protein synthesis (MPS). This study investigated postprandial plasma amino acid (AA) responses of 2 different forms of whey protein isolate (WPI) with iso-caloric and iso-nitrogenous profiles to investigate plasma concentrations of EAA. Methods: In all, 12 healthy men (n = 12) between 19 and 32 years of age were recruited for a randomized, cross-over design, which involved consumption of protein supplements on 2 testing days separated by a 6-day washout period between conditions. On each testing day, subjects consumed either 29.6 g of WPI or WPI + io (whey protein isolate plus Ingredient Optimized Protein ® ) mixed with 236 mL of water. Plasma EAA and branch chain amino acid (BCAA) concentrations were assessed from whole body donated by subjects at pre-consumption and 30, 60, 90, 120, and 180 minutes post consumption. Results: Plasma levels of total EAA concentration was significantly greater in WPI + io at 30, 60, 90, and 120 minutes post consumption ( P  < .01, P  < .001, P  < .01, and P  < .01, respectively). Plasma levels of total BCAA concentration was significantly greater in WPI + io at 30, 60, 90, and 120 minutes post consumption ( P  < .01, P  < .001, P  < .01, and P  < .05, respectively) compared with WPI. For leucine, only WPI + io had elevated levels compared with pre-test at 90 minutes post consumption ( P  < .001). Discussion: Both conditions significantly elevated EAA, BCAA, and leucine from basal levels. However, we conclude that the consumption of the treated WPI significantly raises plasma EAA, BCAA, and leucine to a greater extent compared with WPI with no treatment. Thus, supplementation with WPI that has undergone Ingredient Optimized ® technology may be highly beneficial for those who partake in regular exercise, elderly individuals, or those affected by a reduced sensitivity to amino acids.